2004
DOI: 10.1002/ptr.1387
|View full text |Cite
|
Sign up to set email alerts
|

Free radicals mediated membrane damage by the saponins acaciaside A and acaciaside B

Abstract: Acaciaside A and B, two acylated triterpenoid bisglycoside saponins originally isolated from the funicles of Acacia auriculiformis, are known to have antihelmintic activity. In our previous investigation it was suggested that the conjugated unsaturated system of the saponins is involved in producing the damaging effect of saponins, probably by resulting free radicals that induce membrane damage through peroxidation. Here the interaction of saponins and the microsomal membrane was investigated in the presence a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 12 publications
0
17
0
Order By: Relevance
“…which was susceptible to the purification product of the same plant [14] . The observed antibacterial actions of this extract could be attributed to the presence of saponins, tannins, and alkaloids which have proven antimicrobial properties [15], [16] . It is interesting to note that S.aureus is Gram-positive while the rest are Gram-negative.…”
Section: Discussionmentioning
confidence: 91%
“…which was susceptible to the purification product of the same plant [14] . The observed antibacterial actions of this extract could be attributed to the presence of saponins, tannins, and alkaloids which have proven antimicrobial properties [15], [16] . It is interesting to note that S.aureus is Gram-positive while the rest are Gram-negative.…”
Section: Discussionmentioning
confidence: 91%
“…Conjugated unsaturated system of selected saponins is involved in the formation of free radicals, which induces membrane damage through peroxidation of membranes in helmiths (Nandi et al, 2004). Saponins enhance the cell membrane lipid peroxidation (Babu et al, 1997).…”
Section: Phytochemical Analysismentioning
confidence: 99%
“…In our previous investigations, it was suggested that the conjugated unsaturated system of the saponins is involved in producing the damaging effect of saponins, probably by resulting free radicals that induce membrane damage through peroxidation (Sinha Babu et al 1997). Our findings on the mechanism of action of saponins further revealed that the superoxide anion is probably involved in the expression of membrane-damaging effect of the saponins (Nandi et al 2004). The present data indicate that prior tetracycline treatment enhances microfilaricidal activity of saponins.…”
Section: Pcr Of Microfilaria Samplesmentioning
confidence: 99%
“…These two saponins are known to interact with the membrane, thus, inflicting membrane damage (Sinha Babu et al 1997). Our findings on the mechanism of action of saponins further revealed that superoxide anion is probably involved in the expression of membrane damaging effect of saponins (Nandi et al 2004). Since tetracycline acts on the clearance of Wolbachia, it is of great interest to know whether saponin-induced membrane damage could increase the efficacy of tetracycline on Wolbachia.…”
Section: Introductionmentioning
confidence: 99%